Effect of mycorrhizal inoculation and phosphorus fertilizer on maize root infectivity in three soil series - Aboderin, Adebimpe; Oyediran, Gbade (Journal of Agricultural Sciences (Belgrade), 2024)
An experiment was carried out to examine the influence of mycorrhizal inoculation and phosphorus fertilizer on maize root infectivity in three soil series at Ladoke Akintola University of Technology (LAUTECH), Ogbomoso, Nigeria. The treatments were; three soil series (Gambari, Itagunmodi and Iwo series), three levels of phosphorus fertilizer (0, 30 and 60 kgP2O5/ha) and three levels of mycorrhizal inoculation (0, 10 and 20 g per 15 kg soil). The experimental design used was 3×3×3 factorial in Completely Randomized Design with three replications. Root infectivity was evaluated by grid line intersect method. After harvesting, the phosphorus (P) uptake was determined by P concentration in plant multiplied by total dry weight. Data were analysed using analysis of variance and significant treatment means were compared with Duncan Multiple Range Test at 5% significance level. The results revealed that P uptake was influenced significantly (p < 0.05) by soil series. The order of decrease in P uptake across the soil series were Itagunmodi (0.54 mg/kg) < Iwo series (0.90 mg/kg) < Gambari (2.52 mg/kg). Root infectivity significantly enhanced the uptake of P. The highest root infectivity and highest P uptake was at 20 g inoculation. Mycorrhizal infection levels were depressed by moderate to high rate of soluble phosphorus fertilizer. Thus, increasing levels of phosphate fertilizer stimulate maize root growth but greatly depressed root infection levels.
Keywords: mycorrhizal inoculation, soil series, root infectivity, phosphorus uptake.